2008
DOI: 10.1016/j.mod.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A functional screen for genes involved in Xenopus pronephros development

Abstract: In Xenopus, the pronephros is the functional larval kidney and consists of two identifiable components; the glomus, the pronephric tubules, which can be divided into four separate segments, based on marker gene expression. The simplicity of this organ, coupled with the fact that it displays the same basic organization and function as more complex mesonephros and metanephros, makes this an attractive model to study vertebrate kidney formation. In this study, we have performed a functional screen specifically to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 100 publications
1
5
0
Order By: Relevance
“…This disease is associated with multiple pathways and affects many tissues, such as kidney, liver, heart, and pancreas (38,39), the tissues where mitochondrial FAS II genes are highly expressed. Recent studies that showed dysregulation of Mecr caused abnormalities in Xenopus kidney development (40) are also consistent with the hypothesis that mitochondrial FAS is linked to kidney function.…”
Section: ␤-Hsd8 Expression and Pkdsupporting
confidence: 76%
“…This disease is associated with multiple pathways and affects many tissues, such as kidney, liver, heart, and pancreas (38,39), the tissues where mitochondrial FAS II genes are highly expressed. Recent studies that showed dysregulation of Mecr caused abnormalities in Xenopus kidney development (40) are also consistent with the hypothesis that mitochondrial FAS is linked to kidney function.…”
Section: ␤-Hsd8 Expression and Pkdsupporting
confidence: 76%
“…In vertebrates, SoxFs are involved with vascular development and cardiogenesis, are expressed in structures such as the aortic arch, circulatory system, and pharyngeal arches in addition to parts of the CNS (Zhang et al, 2005; Kyuno et al, 2008). We isolated a single SoxF gene.…”
Section: Resultsmentioning
confidence: 99%
“…Dnajc15 has been suggested to be involved in pronephros development in Xenopus embryos [59], and Camk1d has been associated with type 2 diabetes [60]. Further analysis needs to conducted on these genes to define their potential role in gonad development.…”
Section: Discussionmentioning
confidence: 99%